CRITERIA AND QUALITY INDICATORS OF INFORMATION AND COMMUNICATION TECHNOLOGIES OF LEARNING - Oleg M. Spirin (Інформаційні технології і засоби навчання, 2013)
In the article the concept of information and communication technology and information and communication technology of learning is specified. It is grounded an external and internal criteria of information and communication technologies of learning quality assessment based on experience of information and communication technology quality assessment of the methodical system of informatics teachers vocational training. There are considered the external indexes – design, structural, organizational, communicative and gnostic criteria, and internal – differentiation, individualization, intensification of teaching process and effectiveness of educational activity. There are presented the approaches to assess the indicators for determination of criteria demonstration degree.